De novo assembly and characterization of the transcriptome of a wild edible mushroom Leucocalocybe mongolica and identification of SSR markers. Issue 6 (2nd November 2017) - Lu, Tie; Bau, Tolgor
ABSTRACT: Leucocalocybe mongolica is a prestigious rare wild edible mushroom in Northeast Asia. It is the unique species of the genus and the studying of its phynotype and genome is crucial to genus and species classification. Beyond that, it has high application and ecological value in the industry of food and atmosphere investigation. On account of the fact that transcriptomic and genomic data of L. mongolica lacked in the biological information database, that is a limitation to further study. The transcriptome data were obtained by virtue of Illumina paired-end sequencing technology: 42, 622, 958 clean reads were achieved and 37, 302 contigs were generated. These contigs were subsequently assembled into 13, 821 unigenes. These unigenes were annotated within 7 public databases. The 3914 unigenes were associated with a COG classification. Throughout all of the unigenes, 6642 were classified as three functional groups; 3110 unigenes were selected from KEGG pathways, and taken to further clustering analysis for 5 main categories; 57 genes, potentially involved in terpenoid, steroid, and unsaturated fatty acids biosynthesis were identified and selected for further research. The total number of carbohydrate-active enzymes of L. mongolica is 446 and the number of carbohydrate binding module (CBM) is relatively low. CE11, GT19, GT51, GT56, GH131, GH133, GH135 constitute the characteristic carbohydrate-active enzymes subfamily compared to other edible mushrooms. The characteristic carbohydrate enzymes relative to other mushrooms could play a vital role on the metabolism of nutrients. In these generated sequences, 1860 SSRs were identified and characterized as molecular candidate markers existing L. mongolica .